Kematian Seutuhnya Dalam Pengakuan Gereja Toraja Menurut Pandangan Antropologi Metafisik - Salewa, Wandrio (SOPHIA: Jurnal Teologi dan Pendidikan Kristen, 2020)
Death is a reality that every human being must experience. In death all human power and effort during his life becomes terminated, meaningless and death stops everything. Even so, humans believe in themselves there is something that is not affected by death, namely the soul, so that only the body experiences death. Whether influenced by philosophical thinking or traditional views. The dead body and the immortal soul contain the notion of a soul containing divine elements. The description in this paper focus on understanding death as a whole using a metaphysical anthropology approach. With the research method of literature study and cursory observations, the result show that humans die completely and live completely. Humans experience death in both body and soul. However, on the other hand, in personal relationships with others, it is found that the body and soul remain intact in the memories of others, even though someone’s person has died. The concept og human death as a whole, in the view of metaphysical anthropology, has similarities with complete death, is the recognition of the Toraja church.   Keywords: Death, Body, Spirit, Metaphysical Anthropology, Wholeness and Unity.